The Influence of the Learning Environment on Students’ Motivation in Learning Arabic - M. Izul Islam; Muhamad Hasyim; M. Ilham; M. Zainul Mukhlisin Azhari; M. Hadar Fathul Khairi; Muh. Hafizuddin Alfauzani; M. Syamsul Ma’arif (Indonesian Journal of Education and Science, 2026)
The learning environment has been widely recognized as a critical factor influencing students’ motivation, particularly in the context of Arabic language learning, which involves complex linguistic and sociocultural dimensions. This study aimed to systematically examine how the learning environment has been conceptualized, to identify its key dimensions, and to analyze its influence on students’ motivation in learning Arabic. A qualitative approach using a systematic literature review design was employed. Data were collected from scholarly articles and academic books published between 2015 and 2025, sourced from reputable databases. The selection process followed predefined inclusion criteria, and the data were analyzed using thematic analysis to identify patterns and relationships across studies. The findings revealed that the learning environment is a multidimensional construct consisting of physical, social, psychological, technological, and religious-cultural dimensions. These dimensions were found to interact dynamically in shaping students’ intrinsic and extrinsic motivation. The results also indicated a positive and reciprocal relationship between the learning environment and motivation, where supportive environments enhance student engagement and achievement, while motivated learners contribute to more conducive learning conditions. Furthermore, factors such as teaching strategies, social support, and individual differences were identified as important mediators and moderators in this relationship. In conclusion, this study highlights the importance of designing holistic and supportive learning environments to enhance students’ motivation in Arabic language learning and provides a comprehensive framework for future research and educational practice.